ABORTION: EXPERIENCES AND SENTIMENTS OF WOMEN - Nogueira do Nascimento Gualberto, Sara Virgínia; de Amorim Marçal, Francielton; Santos de Melo, Crisângela; Duarte de Sales, Janayle Kéllen; Pereira Coelho, Hercules; Couto Feitosa, Andréa (Cadernos ESP, 2023)
To know the experience and feelings of women about the abortion process in a Family Health Unit in the municipality of Juazeiro do Norte, Ceará, Brazil. This is an exploratory, descriptive study, with qualitative data, conducted in a family health unit in the municipality of Juazeiro do Norte, Ceará, Brazil. Nine women participated in the study. Data were collected using a semi-structured interview script, and assessed through thematic content analysis. To facilitate the understanding of the results, we chose to organize them into thematic categories, namely: women's knowledge about the causes of abortion and feelings experienced by women who have had an abortion. Abortion is a deeply delicate and challenging experience for women, generating a significant impact and triggering painful feelings before the expectation of having a child and the subsequent loss.
Keywords: Abortion; Feelings; Women